ATP1A3-related disorders: An update. (March 2018) - Carecchio, Miryam; Zorzi, Giovanna; Ragona, Francesca; Zibordi, Federica; Nardocci, Nardo
Abstract: Alternating Hemiplegia of Childhood (AHC), Rapid-onset Dystonia Parkinsonism (RDP) and CAPOS syndrome (cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss) are three distinct, yet partially overlapping clinical syndromes that have long been thought to be allelic disorders. From 2004 to 2012, both autosomal dominant and de novo mutations in ATP1A3 have been detected in patients affected by these three conditions. Growing evidence suggests that AHC, RDP and CAPOS syndrome are part of a large and continuously expanding clinical spectrum and share some recurrent clinical features, such as abrupt-onset, asymmetric anatomical distribution and the presence of triggering factors, which are highly suggestive of ATP1A3 mutations. In this review, we will highlight the main clinical and genetic features of ATP1A3 -related disorders focussing on shared and distinct features that can be helpful in clinical practice to individuate mutation carriers. Highlights: Mutations in ATP1A3 are responsible for a wide phenotypic spectrum of neurological disorders. Abrupt -onset of manifestations and triggering factors are highly suggestive of ATP1A3 mutations. Genotype-phenotype correlation has helped to explain different clinical phenotypes.